(untitled) (KYAMC Journal, 2017)
Background: Body mass index is a valuable tool to assess the nutritional status of an individual. It can be conveniently used to identify those who are underweight, overweight or obese. Objective: To determine the BMI status of medical students. Methods: This cross sectional descriptive study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2009 to June 2010. A total number of 264 students of both sexes, age ranged from 19 to 21 years were included. A structured questionnaire was used to collect and record the information on age, sex, height in meters and weight in kilograms of each subject. The measurements were taken under supervision using a standardized weighing machine, height measuring scale and measuring tape. Body Mass Index (BMI) was calculated using the formula weight (in kilogram)/ height2 (in meter). Using cut off points from World Health Organization (WHO) criteria BMI was classified. Statistical analysis was done by using SPSS version 16. Result: Mean BMI of male students was 21.64 and of female students was 23.52. In this study, the prevalence of overweight was 20.5% and obesity was 4.5% while 63.6% of the students were within normal weight range and 11.3% were underweight. Among the male students 9.35% were underweight, 76.97% were normal weight, 10.07% were overweight, 3.59% were obese and among female students it was 13.6%, 48.8%, 32% and 4.54% respectively. Conclusion: This study reveals that overweight is a rising problem for both male and female medical students. Moreover, overweight and underweight issues are more common in female students. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 472-475